2021
DOI: 10.1097/dss.0000000000002475
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Novel Botulinum Toxin A for Masseter Reduction: A Randomized, Double-Blind, Placebo-Controlled, Optimal Dose-Finding Study

Abstract: BACKGROUND A wide lower face and a square jaw are considered esthetic problems, particularly in Asia. OBJECTIVE To investigate the optimal dose of a novel botulinum toxin (prabotulinum toxin A) for treating masseteric hypertrophy. METHODS Ninety subjects with masseteric hypertrophy were randomly divided into 5 groups and treated with placebo (A, normal saline) or prabotulinum toxin A (B: 24, C: 48, D: 72, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This area did not protrude from the center of the cheek, nor was it in the middle of the cheek area; neither point was clinically meaningful. Hence, before-and-after evaluations of cheek area modifications such as MEDPOR augmentation 37 , soft tissue treatments with botulinum toxins 38 40 , malar-plastic surgery 41 , and changes in soft tissue when treated by mini-screw-assisted rapid palatal expanders 36 could not be precisely assessed using these landmarks. However, in this study, when using the marching cube algorithm to digitize dots on the cheeks (Ch_r, Ch_l) using Program S, the most protruding area could be evaluated, which is clinically significant, and can possibly be applied to the evaluation of the forementioned treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This area did not protrude from the center of the cheek, nor was it in the middle of the cheek area; neither point was clinically meaningful. Hence, before-and-after evaluations of cheek area modifications such as MEDPOR augmentation 37 , soft tissue treatments with botulinum toxins 38 40 , malar-plastic surgery 41 , and changes in soft tissue when treated by mini-screw-assisted rapid palatal expanders 36 could not be precisely assessed using these landmarks. However, in this study, when using the marching cube algorithm to digitize dots on the cheeks (Ch_r, Ch_l) using Program S, the most protruding area could be evaluated, which is clinically significant, and can possibly be applied to the evaluation of the forementioned treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study conducted by Hong et al (2021), the effective dose range for a reduction of the masseter muscle ranged from 48 to 72 units. They also found that gradual reduction was observed up until 12 weeks and after that period, reinjection should be considered for maintaining satisfactory cosmetic effect [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also helps to evaluate the condition of the masseter muscle and surrounding tissues, thus, differential diagnosis. Ultrasound measures muscle thickness which is helpful for the determination of the optimal dose of Botox [ 26 , 30 , 31 , 32 , 33 ]. Magnetic resonance and computerized tomography of the masseter regions are performed commonly for the purpose of differential diagnosis with some attempts to use them for assessments of treatment effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequent BTA or Xeomin [incobotulinumtoxin A (INCO)] injections given at intervals of 3–6 months may be effective in long term management of masseter hypertrophy and contouring of lower face 30,31 . Prabotulinumtoxin A (PRA) in a dosage of 48–72 units followed by reinjection after 12‐weeks is also effective in a dose‐dependent manner; however, higher doses may lead to discomfort during jaw movement 32 . It is important to note that studies which reported on the use of higher doses of BTA are almost always from Asian countries, especially Korea.…”
Section: Dosage Frequency and Efficacymentioning
confidence: 99%
“…30,31 Prabotulinumtoxin A (PRA) in a dosage of 48-72 units followed by reinjection after 12-weeks is also effective in a dosedependent manner; however, higher doses may lead to discomfort during jaw movement. 32 It is important to note that studies which reported on the use of higher doses of BTA are almost always from Asian countries, especially Korea. Our experience is that Caucasian patients achieve acceptable results using 15-30 units per side (Figures 2, 3).…”
Section: Frequent Bta or Xeomin [Incobotulinumtoxin A (Inco)] Injectionsmentioning
confidence: 99%